Microbiological shelf life of fresh, chilled reindeer meat (M. longissimus dorsi) - Wiklund, Eva (Rangifer, 2011)
In this pilot study loin muscles (M. longissimus dorsi) from six reindeer calves (aged 4 months) were used to determine shelf life of fresh, chilled reindeer meat stored at +4 °C, measured as microbiological quality (aerobic microorganisms and Escherichia coli). The loins were collected at boning 3 days post slaughter and divided in five pieces that were randomly assigned to five different storage times; sampling directly after packaging and after chilled storage for 2, 3, 4 and 5 weeks at +4 °C. Samples were vacuum packaged and transported chilled to Hjortens Laboratory in Östersund, Sweden (accredited by SWEDAC according to SS-EN ISO/IEC 17025:2005 for food analysis) where the storage, microbiological sampling and analysis took place according to the protocols of Nordic Committee on Food Analysis (NMKL). The total amount of aerobic microorganisms at the first sampling directly after packaging (three days post slaughter) was 3.4 ± 0.3 log10 CFU/g. After two and three weeks of vacuum packaged chilled storage at +4°C the microbiological quality of the samples was on the border-line to poor (6.8 ± 0.3 log10 CFU/g). At four and five weeks of chilled storage the levels of aerobic microorganisms were significantly highest (P≤0.05) and the limit for acceptable quality of 7 log10 CFU/g aerobic bacteria had been passed (7.3 ± 0.3 log10 CFU/g and 7.8 ± 0.3 log10 CFU/g, respectively). Very few of the reindeer meat samples were contaminated with Escherichia coli bacteria. The results from the present pilot study suggest that storage time for vacuum packaged fresh, chilled reindeer meat should not exceed 3 weeks at a temperature of +4 °C.
Keywords: reindeer meat; microbiology; hygienic quality; shelf life; aerobic plate count; Escherichia coli